2018
DOI: 10.7752/jpes.2018.s3200
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Sports events are currently associated to economic profits and tourism attraction. It is increasingly common for cities to consider local development strategies where sporting events take the center stage. This study analyzes the economic impact of the XVIII Spanish Spring Open Absolute Swimming Championship 2017. It addresses three aspects of economic impact. First, it applies a Cost-Benefit Analysis (CBA) to estimate the economic impact of the event. Moreover, it identifies and describes the socio-demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…It is therefore urgent to define this concept in context, so that researchers can unify criteria, allowing them to compare their analyses. This review mainly found research that focused on sport impacts (Chen and Henry, 2016;Frawley and Van den Hoven, 2015;Malchrowicz-Mosko, et al, 2019), secondly, on economic impacts (Jerkunica et al, 2017;Parra et al, 2018;Salgado et al, 2018) and, thirdly, on urban/infrastructure impacts (Añó et al, 2012;Butel-Ribeiro and Schor, 2017;Parra et al, 2018). Two of the three mentioned (sport and urban/infrastructure) are not found in Preuss and Solberg's (2006) classification.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore urgent to define this concept in context, so that researchers can unify criteria, allowing them to compare their analyses. This review mainly found research that focused on sport impacts (Chen and Henry, 2016;Frawley and Van den Hoven, 2015;Malchrowicz-Mosko, et al, 2019), secondly, on economic impacts (Jerkunica et al, 2017;Parra et al, 2018;Salgado et al, 2018) and, thirdly, on urban/infrastructure impacts (Añó et al, 2012;Butel-Ribeiro and Schor, 2017;Parra et al, 2018). Two of the three mentioned (sport and urban/infrastructure) are not found in Preuss and Solberg's (2006) classification.…”
Section: Discussionmentioning
confidence: 99%
“…De acuerdo con Salgado et al (2018), el texto de la encuesta para los asistentes se estructuró en cuatro partes diferentes con un total de 26 preguntas. La primera parte del cuestionario pretendía identificar si el asistente era residente en la ciudad de celebración del evento al que asistía.…”
Section: Materials Y Métodounclassified
“…Las instituciones públicas han tomado conciencia de este fenómeno, y más allá del innegable interés meramente deportivo que puedan tener, buscan analizar su importancia para el apoyo y promoción de los lugares donde se celebran. En este sentido, son esenciales estudios que permitan captar la dimensión de los eventos deportivos realizados sus flujos económicos en las áreas locales o regionales en las que se centran los eventos de pequeño y mediano tamaño (Salgado, Sánchez, Pérez & Barajas, 2018).…”
Section: Introductionunclassified
“…If we consider the main scientific advances from a global perspective, we see that one of the hot topics with great potential for growth has been the deepening of knowledge on sports mega-events, both in terms of their structure, organisation and main characteristics (Vegara-Ferri et al, 2018;Cerezo-Esteve et al, 2022;Ludvigsen et al, 2022;Reis et al, 2023) and in relation to their different stakeholders (Annear et al, 2019). Among other things, the results obtained in different studies allow a multidimensional analysis of the holding of sporting mega-events and their impacts on society (Barandela et al, 2018). In this sense, it is essential to monitor the evolution and modernisation of societies through new research that increases and differentiates knowledge from different perspectives (Kokolakis et al, 2020;Teixeira et al, 2023b).…”
Section: Introductionmentioning
confidence: 99%